Revealing the Mechanisms of Shikonin Against Diabetic Wounds: A Combined Network Pharmacology and In Vitro Investigation - Meng Tian; Junchao Wu; Qian Du; Jiale Han; Meng Yang; Xiang Li; Mingzhu Li; Xiaofeng Ding; Yeqiang Song (Journal of Diabetes Research)
Conclusion: This study initially revealed the molecular mechanism of SHK in DW by multitarget and multipathway. The PI3K–AKT signaling pathway, MAPK signaling pathway, and AGE-RAGE signaling pathways may be the main pathways of SHK in treating DW.